In vivo tracking of cellular therapeutics using magnetic resonance imaging - Long, Christoper M (2009)
BACKGROUND: The success of many cell-based therapies is highly dependent on the accurate delivery, dosing and trafficking of the cellular therapeutic. In vivo magnetic resonance (MR) cell tracking provides a means to non-invasively and longitudinally evaluate these parameters for cellular therapy. OBJECTIVE: To provide an overview of MR cell tracking and how cellular therapeutics might be improved by utilizing this technology. METHODS: We focused on the technologies utilized for stem cell and immunotherapies in preclinical models of disease. RESULTS/CONCLUSION: New technologies in MR cell tracking will soon take the field beyond preclinical studies and begin to show benefits in clinical trials of novel experimental cell-based therapies.